2013
DOI: 10.5152/balkanmedj.2012.090
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Health Perspective in Sports Medicine: The Trend at the Use of Medications and Nutritional Supplements during 5 Years Period between 2003 and 2008 in Football

Abstract: Objective: To assess the prevalence of medication and nutritional supplement use in male Football Super League players and to observe the long term changes of players' attitudes during 5 years period (4 seasons).Study Design: Retrospective study. Material and Methods:Review and analysis of 4176 doping control forms -declaration reports-about players' medication intake including; Super League, UEFA Cup and the UEFA Champions League matches. Team physician was asked to document all medications and nutritional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Similar outcomes are noted in the literature [27,44]. On the other hand, the study by Sekulic et al reported a similar prevalence of DS use in male and female athletes [45]. These differences between studies are mainly related to cultural norms of the community, including awareness about female football and equality for male and female athletes.…”
Section: Discussionsupporting
confidence: 81%
“…Similar outcomes are noted in the literature [27,44]. On the other hand, the study by Sekulic et al reported a similar prevalence of DS use in male and female athletes [45]. These differences between studies are mainly related to cultural norms of the community, including awareness about female football and equality for male and female athletes.…”
Section: Discussionsupporting
confidence: 81%
“…However, in certain studies conducted with professional athletes in Turkey, it has been seen that the rate of influenza vaccinations are higher than that of the normal population. In the study carried out by Kavukcu et al, with professional footballers, the rate of regular influenza vaccinations among the participants, on a yearly basis, throughout the whole 5-year term of the study, was 75% [24]. This group is the equivalent of the 18-49 age group in our study, where the rate of influenza vaccinations was 26.2%.…”
Section: Discussionsupporting
confidence: 47%
“…This high consumption of medication use in international football raises the questions on whether medication is used for therapeutic reasons only. [55][56][57][58] The use of medication in elite female soccer players, however seems fewer than in adolescent male soccer players during global world contests. 59 The prescription of medications should be consistent with established, recognised pharmacological and pharmacodynamic principles (i.e.…”
Section: Background Information On Management Of Musculoskeletal Injuriesmentioning
confidence: 99%